Synthesis of (V2/3Sc1/3)2AlC i-MAX phase and V2−xC MXene scrolls. Issue 31 (26th July 2019) - Thörnberg, Jimmy; Halim, Joseph; Lu, Jun; Meshkian, Rahele; Palisaitis, Justinas; Hultman, Lars; Persson, Per O.Å.; Rosen, Johanna
Abstract : We report the synthesis and characterization of a new laminated i-MAX phase, (V2/3 Sc1/3 )2 AlC, with in-plane chemical ordering between the M-elements. We also produce V2− x C MXene with only 24 h etching time using HF and MXene scrolls using LiF + HCl. Abstract : We report the synthesis and characterization of a new laminated i-MAX phase, (V2/3 Sc1/3 )2 AlC, with in-plane chemical ordering between the M-elements. We also present evidence for the solid solution (V2− x Sc x )2 AlC, where x ≤ 0.05. Chemical etching of the Al and Sc results in a two-dimensional (2D) MXene counterpart: V2− x C from the latter phase. Furthermore, etching with HF yields single-sheet MXene of flat morphology, while LiF + HCl gives MXene scrolls. We also show a 4× reduction in etching time for (V2− x Sc x )2 AlC compared to V2 AlC, suggesting that traces of Sc changes the phase stability, and make the material more susceptible to etching. The results show a path for improved control of MXene synthesis and morphology, which may be applicable also for other MAX/MXene systems.